RESPON MASYARAKAT TERHADAP PELAKSANAAN PROGRAM BANTUAN RUMAH TIDAK LAYAK HUNI (RTLH) DARI DINAS SOSIAL DI KECAMATAN MUNGKA KABUPATEN LIMA PULUH KOTA PROVINSI SUMATERA BARAT - fathimah maharami; rosmita rosmita (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2019)
This research is motivated by the housing problems among people. In fact, a house is basic need for human beings. It is a place for family reflecting the dignity and asset for its people. This research focuses on The Response of the Society on the Implementation of the Bantuan Rumah Tidak Layak Huni (Housing Donation) from the Social Government Agency of Kecamatan Mungka Lima Puluh Kota. This research aims to know The Response of the Society on the Implementation of the Bantuan Rumah Tidak Layak Huni (Housing Donation) from the Social Government Agency of Kecamatan Mungka Lima Puluh Kota. This thesis uses quantitative method. Data is analyzed based on correlations coefficient product moment technique using the SPSS 21. Data is collected from questionnaires and documentation. The populations are all people receiving the housing donation program in Kecamatan Mungka Lima Puluh Kota consisting of 53 people. The samples are selected based on total sampling. This thesis finds that there is an effect of the society’s attitude with the coefficient about 0.814 (r = 81.4%) and society’s behavior about 0.979 (r=97.9%) in the implementation of the program. This means that the independent variable (response of the society in the attitude and behavior) has a strong effect to the dependent variable (implementation of the program). This can be seen from the score of the effect in in the interval ranges 0.80 -1.000 and determination coefficient score is about 0, 965 or 96.5%. This thesis concludes that The Response of the Society has an effect on the Implementation of the Bantuan Rumah Tidak Layak Huni (Housing Donation) Program from the Social Government Agency of Kecamatan Mungka Lima Puluh Kota.